Diagnostic utility of the Elecsys anti-CCP assay in patients with rheumatoid arthritis. Issue 4 (July 2014) - Ye, Huiming; Chen, Falin; Yan, Shuidi; Zhang, Yan; Fang, Zanxi; Su, Xiaosong; Cai, Weicheng; Zhang, Zhongying
Abstract Objective. The automatic anti-cyclic citrullinated peptide (anti-CCP) antibodies assay offered great advantages over traditional methods in terms of improved precision, reliability, technical simplicity, short turnaround time and high-speed throughput. In this study, we evaluated the main technical performance and diagnostic accuracy of the first automatic anti-CCP assay approved in China. Methods. The study comprised 106 rheumatoid arthritis (RA) patients, 203 non-RA rheumatic disease controls and 46 healthy persons. Anti-CCP, rheumatoid factor (RF), α1-acid glycoprotein, C-reactive protein and erythrocyte sedimentation rate were measured and compared. The precision, reference intervals for Chinese population and cut-off value for RA diagnosis, as well as the suitable diluent for anti-CCP were assessed. The positive rate and score of anti-CCP were compared with RF and acute-phase reactants, according to the new RA criteria. Results. Within- and between-run imprecision, expressed as the coefficient of variation, were 0.47–1.36% and 1.15–2.63%, respectively. Upper 95% reference limit of anti-CCP in healthy Chinese was 8.8 U/mL. The area under curve of the receiver operating characteristic(ROC) for anti-CCP and RF were 0.882 (95% CI 0.833–0.930) and 0.844 (95% CI 0.792–0.897), respectively. Based on the cut-off value set by ROC, compared to RF, anti-CCP had higher sensitivity (96.8% vs. 78.3%) and specificity (90.9% vs. 70.7%). With 17 U/mL set as the optimal cut-off for anti-CCP, the total positivity of anti-CCP was comparable to that of RF (76.4% vs. 75.5%), but the high-positivity rate of anti-CCP was significantly higher (74.5% vs. 62.3%, p < 0.005). Conclusions. Our results confirm anti-CCP as a more sensitive and specific marker than RF for the diagnosis of RA. The diagnostic performance of the Elecsys anti-CCP assay makes it a useful adjunct to clinical practice in the Chinese population.